Consequences of Workplace Ostracism: A Meta-Analytic Review - Li, Miaomiao; Xu, Xiaofeng; Kwan, Ho Kwong (Frontiers in Psychology, 2021)
Workplace ostracism, which is regarded as “social death,” is rampant in organizations and has attracted significant research attention. In this study, we extend the workplace ostracism research by conducting a meta-analysis of the relationships between workplace ostracism and its consequences. We also explore the moderating effects of national culture (i.e., collectivism vs. individualism) and the mediating effects of organization-based self-esteem (OBSE). The results from a meta-analytic model of 95 independent samples (N = 26,767) reveal that exposure to workplace ostracism is significantly related to individuals’ attitudes, well-beings, and behaviors. Moreover, the effects of workplace ostracism on belonging, job satisfaction, emotional exhaustion, organizational citizenship behavior (OCB) toward individuals (OCBI), organizational deviance, and interpersonal deviance are stronger in individualistic contexts than in collectivistic contexts. Furthermore, the relationships between workplace ostracism and organizational identification and OCB are stronger in collectivistic contexts than in individualistic contexts. Our meta-analytical structural equation modeling also provides evidence for the mediating effects of OBSE on the relationships between workplace ostracism and organizational commitment, job satisfaction, and job performance. The implications and limitations of our study and future research directions are also discussed.